2000
DOI: 10.1021/jp0011286
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of Electrochemically Deposited Cu on p-GaAs(100) in H2SO4 Solution by In Situ Surface-Sensitive X-ray Absorption Fine Structure Measurements

Abstract: The local structures of electrochemically deposited Cu on p-GaAs(100) of various coverages in 0.1 M H 2 SO 4 solution containing 0.1 mM CuSO 4 have been investigated by in situ surface-sensitive X-ray absorption fine structure (XAFS). The Cu K-edge extended X-ray absorption fine structure (EXAFS) and X-ray absorption near-edge structure (XANES) were obtained over a wide range of coverages, i.e., several monolayers down to 1/20 monolayer. The results of multishell parameter fitting of EXAFS data showed that Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 61 publications
1
23
0
1
Order By: Relevance
“…EXAFS has proven to be a powerful and flexible characterization technique and has been applied to studies of heteroepitaxial film growth, 2123 nanoparticle characterization, 49−51 and potential-dependent studies of electrocatalysts. 5254 The in situ EXAFS measurements presented here are unique in their ability to provide a structural model at each stage of the deposition of Cu on Au nanoparticles during the deposition.…”
Section: Introductionmentioning
confidence: 99%
“…EXAFS has proven to be a powerful and flexible characterization technique and has been applied to studies of heteroepitaxial film growth, 2123 nanoparticle characterization, 49−51 and potential-dependent studies of electrocatalysts. 5254 The in situ EXAFS measurements presented here are unique in their ability to provide a structural model at each stage of the deposition of Cu on Au nanoparticles during the deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption edge energy in the XANES spectra reflects the electronic state of the excited atom [7,14,15,[20][21][22]. The position of the absorption edge is sensitive to the oxidation state of the element.…”
Section: Resultsmentioning
confidence: 99%
“…XANES (X-ray absorption near edge structure) and EXAFS (extended X-ray absorption fine structure) are particularly useful techniques for providing such structural information in dispersed and amorphous materials. However, to date, only a few investigations had been carried out using XANES and EXAFS results for characterizing copper deposited layers and these are essentially centered on the structure of underpotential and overpotential formed materials [11][12][13][14][15]. Such an analysis is useful for optimizing the deposition process, to obtain a more adequate structure and composition for the deposited layer.…”
Section: Introductionmentioning
confidence: 99%
“…Both theoretical predictions [1][2][3][4][5][6] and experimental results [6][7][8][9][10][11][12][13][14] have indicated that lattice constant of small metallic nanoclusters is smaller than that of the corresponding bulk crystals. However, the systematic study on the size dependent lattice constant change of metal nanoclusters has yet to be carried out because of the difficulty in precise control of the cluster size.…”
Section: Introductionmentioning
confidence: 99%